Marketplace Penjualan Produk UMKM Kabupaten Bireuen Sebagai Portal Community Marketing Berbasis Web - T Irfan Fajri, Mutasar, Intan Tursina (Jurnal Elektronika dan Teknologi Informasi, 2023)
The advancement of online marketing has opened up extensive opportunities for Small and Medium Enterprises (SMEs) to expand their reach to international markets. This research aims to create a comprehensive sales information system for showcasing and selling unique handicraft products through a web portal, administered by designated personnel. This system will not only facilitate the marketing of fashion items but also emphasize the promotion of handmade crafts.